Pengaruh Terapi Kidung Wahyu Kalaseba Terhadap Resiliensi Psikologis Menghadapi Pandemi Covid-19 Bagi Mahasiswa Prodi Tasawuf dan Psikoterapi Universitas Islam Negeri Walisongo - Fitriyati, Hikmatun Balighoh Nur (Piwulang : Jurnal Pendidikan Bahasa Jawa, 2019)
After being ranked first in the global burden of diseases, mental health problems have increased by 70-100% in various countries due to the Covid-19 pandemic. Reported by WHO (2020), many people experience psychological complaints such as anxiety, stress, frustration, and depression. The education sector is the largest community group affected by mental health problems due to the Covid-19 pandemic. Many studies have stated that students experience stress, anxiety, depression, and decreased productivity due to various policies during the Covid-19 pandemic. Resilience has a strong influence on a person's psychological well-being. Resilience is the ability to adapt a person in a bad and threatening situation. Therefore, it is necessary to increase psychological resilience to be able to deal with the Covid-19 pandemic. This study seeks to improve the psychological resilience of students of the Prodi Tasawuf dan Psikoterapi with the Kidung Wahyu Kalaseba therapy. Kidung Wahyu Kalaseba is a Javanese song that has Javanese-Islamic religious values ​​inherited from Walisongo, especially Sunan Kalijaga. The study was conducted on 30 samples of students of the Prodi Tasawuf dan Psikoterapi through a one group pretest-posttest experimental design. Through t test analysis and regression test, it was found that the Kidung Wahyu Kalaseba therapy had a significant effect in increasing psychological resilience, 25.24% with a significance level (0.002). This research is an effort to explore the value of indigenous psychotherapy from Javanese-Muslims culture that can be used to overcome mental health problems.